The Application of Quizizz with Flipped Classroom Teaching Method in Large Pharmacology Class - Phetmanee, Thidarat; Pradubyat, Nalinee (Interprofessional Journal of Health Sciences, 2023)
Pharmacology is a fundamental course in the pharmacy curriculum. In the course, students are expected to apply the principles of pharmacodynamics and pharmacokinetics, along with understanding the concepts of drug interactions and adverse drug reactions for later topics in the course. Every year, a significant number of third-year students enroll, making the teaching environment challenging due to its size and limiting student-instructor interactions. To address this, we integrated the gamification tool, Quizizz, with the flipped classroom approach to enhance student engagement. Our study aimed to gauge student satisfaction with this hybrid method. In this study, we focused on topics including the principles of pharmacology and pharmacogenomics, pharmacodynamics, pharmacokinetic processes, and concepts of drug interactions and adverse reactions. The teaching method employed was a combination of Quizizz and the flipped classroom approach. The online questionnaire collected general information, gauged student satisfaction with the integration of Quizizz and the flipped classroom method and sought suggestions from the participants. Data was collected from 148 students in post-classroom session. Overall, students reported high satisfaction levels, though some found the session duration lengthy. The use of Quizizz was particularly well-received, and students appreciated the teaching content. Notably, students from diverse educational backgrounds expressed similar satisfaction levels, suggesting the method's broad applicability. In conclusion, our study underscores the effectiveness of combining Quizizz with the flipped classroom model, especially in large classroom settings.